AWARENESS OF HERPANGINA AND ITS MANAGEMENT AMONG DENTAL STUDENTS - hirunavakarasu, Reshma T; Ganapathy, Dhanraj; Rohinikumar, Subhashree (International Journal of Psychosocial Rehabilitation, 2019)
Herpangina or otherwise known as hand-foot and mouth disease is caused by enteroviral infection and are two common related clinical syndromes. This diseases are mostly seen in paediatric population . It is occasionally seen among adult patients. Herpangina is caused by one particular strain of coxsackie virus A and Enterovirus -A71 .The aim of the study was to determine if dental students are aware of the various managements done for herpangina. A survey with 9 close ended questions and 3 multiple choice questions were formed and distributed to 100 dental students respectively. Their responses will determine the level of awareness of students regarding the management of herpangina. The questions elicited awareness on the various aspects of Herpangina disease among dental students..These responses to these questions were tabulated and analysed. 55% of the respondents said Herpangina affected people aged between 3-10yrs . 75% respondents said Herpangina is caused by Group A coxsackieviruses followed by 20% said Streptococcusand 5% said Staphylococcus are responsible. 83% of respondent prescribed antivirals followed by analgesics15% and 2% used antibiotics to treat Herpangina.The awareness about the management strategies of Herpangina among dental students was moderate.Awareness of dental students can always be enhanced by promoting more educational programmes regarding various diseases such as herpangina. It is important as they will play an important role in delivering better health care in the future.